2015
DOI: 10.1038/srep17204
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and inter-nucleosomal interactions of the histone H4 tail revealed with a human nucleosome core particle with genetically-incorporated H4 tetra-acetylation

Abstract: Post-translational modifications (PTMs) of histones, such as lysine acetylation of the N-terminal tails, play crucial roles in controlling gene expression. Due to the difficulty in reconstituting site-specifically acetylated nucleosomes with crystallization quality, structural analyses of histone acetylation are currently performed using synthesized tail peptides. Through engineering of the genetic code, translation termination, and cell-free protein synthesis, we reconstituted human H4-mono- to tetra-acetylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 61 publications
1
77
0
Order By: Relevance
“…We synthesized the full-length histone H4 protein with site-specific acetylations at K5 and K8 on a milligram scale [22], and used it as the antigen. Through screening with ELISA and Western blot, we successfully obtained two hits of hybridoma (1A9D7 and 2A7D9) that recognize the histone H4 proteins containing di-acetylation of K5acK8ac (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We synthesized the full-length histone H4 protein with site-specific acetylations at K5 and K8 on a milligram scale [22], and used it as the antigen. Through screening with ELISA and Western blot, we successfully obtained two hits of hybridoma (1A9D7 and 2A7D9) that recognize the histone H4 proteins containing di-acetylation of K5acK8ac (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The full-length human H4 protein containing acetyl residue at K5 and K8 (H4K5acK8ac) was synthesized in a cell-free system essentially as previously described [22,56] and used to immunize mice. Generation, selection, and purification of antibodies were performed as previously described [24], with the following modifications.…”
Section: Methodsmentioning
confidence: 99%
“…In several cases, regions of intrinsic structural disorder have been shown to act as regulatory elements and are often targets of modification (1416). To account for the importance of these unresolved sites, we used measures of intrinsic disorder defined by the IUPred application (17).…”
Section: Methodsmentioning
confidence: 99%
“…This parameter related to atomic thermal motion is expressed as a probability density function of atomic displacements from the mean position. It has been reported that tetra-acetylation of H4 histones significantly increases the B factors of wrapped DNAs in the vicinity of the tetraacetylated N-terminal tail of inter-and intra-nucleosomal H4 (Wakamori et al, 2015). From this observation and biochemical assays, it is suggested that H4 tetra-acetylation impairs the self-association of nucleosome core particles by changing the interactions of the H4 tail with DNA.…”
Section: Introductionmentioning
confidence: 92%